EDUKASI MENGELOLA KEUANGAN BAGI PELAKU UMKM DI LINGKUNGAN UNIVERSITAS KRISTEN INDONESIA - Riwandari Juniasti Purnama; Fery Tobing; Edison Siregar; Trihanna Kezya Rima; Belinda Oktavian (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2024)
This PKM aims to overcome the problems faced by MSMEs in the UKI environment (canteen) when students are on holiday by focusing on education on managing MSME business finances. When students are on holiday, cafeterias face reduced revenues, inventory surpluses, financial risks, and growth constraints. Therefore, through PKM, we try to overcome this problem through an educational approach. The education carried out is education regarding financial management, simple bookkeeping, digital payment solutions, and online platform activation. From the results of discussions held during the activity, it was found that the majority of participants had not activated online sales using certain platforms, had not separated personal and business finances, had not kept bookkeeping for their business activities, and were still hesitant to use Qris as an alternative payment from buyers. After counseling, participants stated that they wanted to do good bookkeeping, wanted to make sales online, and wanted to use Qris. Continuous assistance is needed so that participants can increase their canteen income through online sales so that when students are on holiday there is no decrease in income, and assistance is needed so that participants can keep their business bookkeeping well so they can know whether their business is profitable and efficient. As well as the need for monitoring the use of Qris from the bank where participants open Qris so that any problems related to Qris can be resolved immediately. Keywords: Education, Financial Management, MSMEs